Sliding Hip Screw and Side Plate for Intertrochanteric Hip Fractures. Issue 1 (2022) - Shih, Yushane; Bartschat, Nicholas I.; Cheng, Edward Y.
Abstract : Background: For stable intertrochanteric hip fractures, treatment commonly involves the use of a sliding hip screw. Intertrochanteric hip fractures are increasingly common as the population ages and lives longer. More than 250, 000 hip fractures occur per year in the United States1 . The mortality rate within the first year following operative treatment ranges from 14% to 27.3%2, 3 . Early surgical repair within 48 hours of injury is associated with a lower risk of mortality2, 4, 5 . The goals of surgical treatment are restoration of coronal plane alignment without varus angulation and early patient mobilization. Description: The sliding hip screw procedure can be divided into (1) preoperative planning; (2) patient positioning; (3) C-arm setup; (4) closed reduction of fracture; (5) sterile preparation and draping; (6) lateral hip approach; (7) guide pin insertion; (8) triple-reaming the proximal aspect of the femur; (9) sliding hip screw insertion into the femoral neck and head; (10) side plate insertion, engaging the sliding hip screw, and fixation to the femur; (11) lag compression screw insertion (if appropriate); and (12) final fluoroscopic images and wound closure. Alternatives: Intertrochanteric hip fractures must be surgically treated to avoid morbidity and increased risk of mortality. Nonoperative treatment is occasionally indicated in nonambulatory patients or those with high perioperative risk. If treated surgically, a common alternative implant option includes the intramedullary nail. Finally, for severely comminuted fractures or failed internal fixation, total hip arthroplasty may be necessary. Rationale: Sliding hip screws are as effective as intramedullary nails and often less costly6 . In general, the quality of fracture reduction is more critical than the choice of implant7 . A prospective study found no significant difference in walking ability with either sliding hip screws or intramedullary nails for stable intertrochanteric fractures8 . Expected Outcomes: By 6 months, the majority of fractures will have healed; according to a prospective randomized study, 91% of stable fractures and 85% of unstable fractures had achieved radiographic union by that time9 . Another study showed radiographically healed fractures in all 106 patients treated with sliding hip screws at median follow-up of 13.6 months8 . Important Tips: Watch out for comminution of the greater or lesser trochanter, which may require supplemental fixation. Prior to completely reflecting the vastus lateralis muscle, control the bleeding from any perforators with use of 2-0 silk ties. This prevents recurrent bleeding, which often occurs if only cautery is utilized to coagulate these vessels. Utilize a 4.5-mm drill hole in the lateral cortex of the femur in order to allow for minor adjustments of the anterior femoral neck guide pin; otherwise, the pin will be held tightly and continue to be bound in the same direction by the lateral cortex on repeated attempts. If the guide pin is inadvertently withdrawn along with the reamer after reaming, a lag screw may be placed backward in the newly reamed hole and the guide pin passed back through the lag screw to reposition it. Extracapsular hip fractures should be carefully scrutinized for signs of instability, such as lateral wall comminution or reverse obliquity. The fracture may displace posteriorly when the patient is supine on the fracture table. While placing the guidewire, multiple entry attempts can weaken the lateral cortex and propagate the fracture into the subtrochanteric region. Superior placement of the lag screw results in poor tip-apex distance and a higher chance of screw cut-out. Be careful to prevent guidewire penetration into the hip joint. Loss of reduction or femoral head malrotation may occur during lag screw insertion. Acronyms & Abbreviations: AP = anteroposterior fx's = fractures IMN = intramedullary nail IV = intravenous PDS = polydioxanone suture SHS = sliding hip screw TFL = tensor fascia lata